P186 Improving diagnosis of gonorrhoea: a service improvement project. (30th June 2016) - Street, Emma; Short, Lindsay; Boyd, Gavin
Abstract : Background: With rising rates of gonorrhoea and increasing resistance, accurate diagnosis and appropriate use of antibiotics has become increasingly important. In response to this, we have focussed service improvement in our sexual health service (site 1= GUM clinic, site 2 = integrated clinic) over the past 5 years on gonorrhoea. Our main focus has been on the high level of NAAT positive, culture negative samples- was this related to false positive tests or failed culture or both. This prompted a review of how samples were handled and, in particular, the time period between sample taking for culture and arriving within the lab. We have refined procedures to improve uptake of culture testing, culture positivity and finally the addition of supplementary testing for all positive NAAT testing in 2015. Aim: To review gonorrhoea diagnosis over a 5 year period, exploring the issue of NAAT positive, culture negative samples. Methods: yearly audit of gonorrhoea diagnoses Results: Discussion: Gonorrhoea diagnoses have dramatically declined between 2014 and 2015 due to the introduction of supplementary testing to remove the issue of false positive results. We have improved the uptake of culture testing in the era of self-taken NAAT testing and improved culture positivity rate with simple changes in the processing of samples.